Microbiome-derived bacterial lipids regulate gene expression of proinflammatory pathway inhibitors in systemic monocytes - Mihori, Saki; Nichols, Frank; Provatas, Anthony; Matz, Alyssa; Zhou, Beiyan; Blesso, Christopher N.; Panier, Hunter; Daddi, Lauren; Zhou, Yanjiao; Clark, Robert B. (Frontiers in Immunology, 2024)
How the microbiome regulates responses of systemic innate immune cells is unclear. In the present study, our purpose was to document a novel mechanism by which the microbiome mediates crosstalk with the systemic innate immune system. We have identified a family of microbiome Bacteroidota-derived lipopeptidesthe serine-glycine (S/G) lipids, that are TLR2 ligands, access the systemic circulation, and regulate proinflammatory responses of splenic monocytes. To document the role of these lipids in regulating systemic immunity, we used oral gavage with an antibiotic to decrease the production of these lipids and administered exogenously purified lipids to increase the systemic level of these lipids. We found that decreasing systemic S/G lipids by decreasing microbiome Bacteroidota significantly enhanced splenic monocyte proinflammatory responses. Replenishing systemic levels of S/G lipids via exogenous administration returned splenic monocyte responses to control levels. Transcriptomic analysis demonstrated that S/G lipids regulate monocyte proinflammatory responses at the level of gene expression of a small set of upstream inhibitors of TLR and NF-κB pathways that include Trem2 and Irf4. Consistent with enhancement in proinflammatory cytokine responses, decreasing S/G lipids lowered gene expression of specific pathway inhibitors. Replenishing S/G lipids normalized gene expression of these inhibitors. In conclusion, our results suggest that microbiome-derived S/G lipids normally establish a level of buffered signaling activation necessary for well-regulated innate immune responses in systemic monocytes. By regulating gene expression of inflammatory pathway inhibitors such as Trem2, S/G lipids merit broader investigation into the potential dysfunction of other innate immune cells, such as microglia, in diseases such as Alzheimer's disease.